Akuntabilitas Perdata Triadik BPJS, Rumah Sakit, dan Pasien dalam Penyelesaian Pending Klaim Jaminan Kesehatan Nasional - Khalid, Hasabuddin; Adha Hamzah, Yuli; Ikhtiari, Athifa (Al-'Adl, 2026)
The phenomenon of pending claims in the National Health Insurance (JKN) system has been widely studied from administrative and health management perspectives. However, no study has systematically examined the civil law accountability structure within the triadic legal relationship among BPJS Kesehatan, hospitals, and patients—particularly in terms of contractual default (wanprestasi) and civil liability for unlawful acts (perbuatan melawan hukum/PMH). This normative legal study employs a statute approach and a conceptual approach, analysing primary legal materials including the Indonesian Civil Code (KUHPerdata), Law No. 40 of 2004 on the National Social Security System, Law No. 44 of 2009 on Hospitals, Law No. 17 of 2023 on Health, and Presidential Regulation No. 59 of 2024 on the JKN Program. The study finds that pending claims constitute a contractual vulnerability that may escalate into wanprestasi by BPJS when hospitals have submitted complete documentation yet payment is delayed beyond the 15-working-day statutory limit. Conversely, hospitals may be liable for wanprestasi when administrative non-compliance triggers claim suspension. Moreover, should service quality deteriorate as a consequence of pending claims, hospitals remain independently liable to patients under Article 1365 of KUHPerdata, irrespective of the underlying contractual dispute with BPJS. The novelty of this study lies in constructing a hierarchical triadic civil liability framework and in identifying four critical contractual gaps in the existing JKN cooperation agreement that perpetuate recurring civil disputes. These findings contribute to the reformulation of JKN contractual architecture toward a more equitable, transparent, and patient-protective legal framework.